Dimensions of manic symptoms in youth: psychosocial impairment and cognitive performance in the IMAGEN sample. (28th May 2014) - Stringaris, Argyris; Castellanos‐Ryan, Natalie; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L.; Bromberg, Uli; Büchel, Christian; Fauth‐Bühler, Mira; Flor, Herta; Frouin, Vincent; Gallinat, Juergen; Garavan, Hugh; et al.
<x xml:space="preserve">Abstract</x> Background It has been reported that mania may be associated with superior cognitive performance. In this study, we test the hypothesis that manic symptoms in youth separate along two correlated dimensions and that a symptom constellation of high energy and cheerfulness is associated with superior cognitive performance. Method We studied 1755 participants of the IMAGEN study, of average age 14.4 years (SD = 0.43), 50.7% girls. Manic symptoms were assessed using the Development and Wellbeing Assessment by interviewing parents and young people. Cognition was assessed using the Wechsler Intelligence Scale For Children (WISC‐IV) and a response inhibition task. Results Manic symptoms in youth formed two correlated dimensions: one termed exuberance, characterized by high energy and cheerfulness and one of undercontrol with distractibility, irritability and risk‐taking behavior. Only the undercontrol, but not the exuberant dimension, was independently associated with measures of psychosocial impairment. In multivariate regression models, the exuberant, but not the undercontrolled, dimension was positively and significantly associated with verbal IQ by both parent‐ and self‐report; conversely, the undercontrolled, but not the exuberant, dimension was associated with poor performance in a response inhibition task. Conclusions Our findings suggest that manic symptoms in youth may form dimensions with distinct correlates. The results are in keeping with previous findings about superior performance associated with mania. Further research is required to study etiological differences between these symptom dimensions and their implications for clinical practice.